Scorpio: A biomimetic reconfigurable rolling–crawling robot. (8th September 2016) - Tan, Ning; Mohan, Rajesh Elara; Elangovan, Karthikeyan
This paper presents the bio-inspired design, realization, and validation of a reconfigurable rolling–crawling robot. The developed platform is able to mimic Cebrennus rechenbergi, a species of huntsman spider which can crawl and roll using only its legs. Mechanical design, control architecture, and actuator selection strategies targeting platform miniaturization are presented in detail. The navigating and autonomous capabilities of the robot are examined in two facets: (1) recovery behaviors where a robot in a previously unknown state after a fall recovers autonomously to a known standing gait state using Inertial Measurement Unit (IMU); and (2) terrain perception where the robot is capable of autonomously assessing the characteristics of the terrain and chooses the appropriate morphology and locomotion mode in relation to the perceived terrain.